Caudal cruciate ligament avulsion at its origin in a dog - KRYSTALLI, A.A.; PRASSINOS, N.N.; MANTIS, P. (Journal of the Hellenic Veterinary Medical Society, 2019)
Caudal cruciate ligament (CaCL) rupture is uncommon in dogs and usually occurs with a concurrent rupture of the cranial cruciate ligament (CrCL). A 10-month-old cross-bred dog was presented with left hind limb lameness. Orthopaedic examination revealed positive craniocaudal drawer sign in the left stifle. Arthrotomy confirmed CrCL rupture, and showed CaCL avulsion fracture at its origin. The stifle was stabilized using extracapsular lateral fabellotibial suture. Eight months postoperatively the dog was free of obvious lameness and remained sound until the last re-evaluation (3 years). This case raises the possibility that restoration of the CaCL function is not always essential for animals’ successful outcome.